Virtual first: implementation of a novel sleep telehealth platform in the United States military - Wickwire, Emerson M.; Collen, Jacob; Capaldi, Vincent F.; Assefa, Samson Z.; Jones, Rachell; Williams, Scott G.; Thomas, Connie L.; Williams, Daniel C.; Albrecht, Jennifer S. (Frontiers in Sleep, 2024)
Background. There is a gross shortage of sleep specialist providers within the military health system. Telehealth and mobile health represent promising approaches to increase access to high quality, cost-effective care in the U.S military.Objectives. This paper reports findings from a mixed-methods clinical implementation study of a novel sleep telehealth platform at two military treatment facilities in the National Capitol Region. The platform includes a mobile app and integrated wearable sensors (i.e., a commercial off-theshelf sleep tracker [Fitbit]). The primary purpose was to evaluate the implementation of a tenday remote monitoring assessment and provision of evidence-based sleep treatment recommendations to patients and providers. In addition, we sought to observe, in an exploratory manner, subsequent engagement with the app during five days of personalized sleep education and training.Methods. Patients with sleep problems completed an intensive ten-day remote monitoring assessment that included a baseline intake questionnaire, daily sleep diaries, twice daily symptom surveys, and Fitbit. Based on this assessment, patients received personalized assessment results. Concurrently, a provider report was generated that included provisional diagnoses and evidence-based treatment recommendations. Next, participants gained access to personalized sleep education and trainings within the mobile app. Within an established implementation science framework, outcomes were assessed via behavioral adherence (engagement with the app) and separate questionnaires for patients and providers. Last, we conducted four focus groups with patients and twelve key informant interviews with primary care managers (PCMs) and economic stakeholders to seek feedback and recommendations for future directions.Results. Two hundred and seventy patients participated in the study. Using validated research questionnaires, participants reported high-risk for obstructive sleep apnea (65.6%), moderate to severe insomnia (38.2%), and moderate to severe daytime sleepiness (38.5%), and moderate to severe anxiety (14.1%) and depressive (20.4%) symptoms. Total sleep time was 6.6 (SD=1.8) hours based on sleep diaries and 6.1 (SD=1.8) hours based on Fitbit. Regarding implementation, reach, effectiveness, adoption, implementation, and maintenance were all notably high, based on quantitative and qualitative data from participants and PCMs.Conclusions. Sleep telehealth and mobile health represent promising approaches to increase access to cost-effective, evidence-based care for sleep disorders in the U.S. military.